(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article is devoted to methodological approaches and conceptual foundations in the definition of secularism in Western political thought. It is well known that the concepts of secularism and secularism are formed and developed due to the historical, socio-political, economic and cultural characteristics of each society. Various factors, social transformations and changes in the role of religion in the public space make their own adjustments to the content of these concepts. In this connection, in this article, the authors consider the main two main trajectories or two strategies for managing the relationship between religion and politics, which influenced the models of secularism in the modern world. The article provides a clear explanation and distinction between the concepts of «secularism», «the principle of secularism», «secularization». The authors analyze the main models and interpretations of secularism and socio-political factors that influence a certain model of secularism. The article also discusses the current religious situation and policy of the Republic of Kazakhstan in the field of religion. The authors analyze the experience of state policy in determining the principles and criterion of secularism in Kazakhstan and provide recommendations for improving the definitions of secularism principles. Kew words: secularism, secularity, state policy, religion, principle, Kazakhstan.